Pharmacokinetic and pharmacodynamic evaluation according to absorption differences in three formulations of ibuprofen - Shin D (Drug Design, Development and Therapy, 2017)
Dongseong Shin,1 Sook Joung Lee,2 Yu-Mi Ha,3 Young-Sim Choi,3 Jae-Won Kim,3 Se-Rin Park,3 Min Kyu Park3 1Clinical Trials Center, Gachon University Gil Medical Center, Incheon, 2Department of Rehabilitation Medicine, 3Department of Clinical Pharmacology and Therapeutics, Dong-A University College of Medicine and Hospital, Busan, South Korea Objective: Prostaglandin E2 (PGE2) synthesis is modulated by COX2. Changes in PGE2 could be used to quantify the COX2 inhibition after ibuprofen administration. This study investigated the pharmacokinetic and pharmacodynamic relationships for COX2 inhibition according to three formulations of ibuprofen in healthy male subjects.Materials and methods: A randomized, open-label, single-dose, three-treatment, six-sequence crossover study was performed in 36 healthy South Korean male volunteers. Enrolled subjects received the following three 200 mg ibuprofen formulations: ibuprofen arginine, solubilized ibuprofen capsule, and standard ibuprofen. Pharmacokinetic and pharmacodynamic blood samples were collected for 16 hours following treatment. For pharmacodynamic evaluations, lipopolysaccharide (LPS)-induced PGE2 inhibition at each time point compared to predose was measured. Noncompartmental analysis was used for pharmacokinetic assessment, and time-weighted average inhibition (WAI) of PGE2 was applied to the pharmacodynamic evaluation.Results: After a single oral dose of the ibuprofen formulations, the median times to maximum concentration were 0.42, 0.5, and 1.25 hours in ibuprofen arginine, solubilized ibuprofen capsule, and ibuprofen, respectively. The maximum observed plasma concentration was lower in ibuprofen, and the area under the plasma concentration–time curve was comparable among the three formulations. A significant difference was observed between fast-acting formulations and standard ibuprofen tablets for both maximum concentration and time taken to reach it. Individual formulations had an effect on PGE2 WAI during the 8 hours following treatment, resulting in significantly lower WAI in standard ibuprofen: ibuprofen arginine 18.4%, solubilized ibuprofen capsule 18.4%, and standard ibuprofen 11.6%.Conclusion: Rapid absorption and higher peak concentration were observed in ibuprofen arginine and the solubilized ibuprofen capsule. Additionally, fast-acting formulations had more predominant inhibitory activity on the COX2 enzyme. Keywords: ibuprofen, different formulation, COX2-inhibitory effects